Alat Bantu Shalat Bagi Disabilitas Tunarungu Berbasis Gyroscope Mpu6050 - Dwi Purnama Sari; Meilia Safitri; Wisnu Kartika; Erika Loniza (Program Studi Teknik Elektro Universitas Khairun, 2022)
A deaf person is someone who has lost the ability to hear so that it hinders the process of language information through his listeners. In Indonesia, most of the population is Muslim and has more than 13,000 people with hearing impairments.In carrying out congregational prayers, it is difficult for the deaf to follow the instructions of the priest's movement. This study aims to make prayer aids technology for the Deaf is to assist in performing congregational prayers. The method used in this tool is to provide notifications in the form of different vibrations at every change in the priest's movement to the Deaf community. The device control system uses Arduino nano FT232RL FTDI FT232. The communication module uses HC-12 SI4463, with 433.4 – 473.0 MHz wireless frequency. The MPU6050 gyroscope sensor is employed for detecting changes in angle or motion, and a micro vibrator motor is used as a vibration indicator. Based on the conducted test, the designed Bracelet performed excellent results. It runs according to its working principle where the Bracelet used by the Imam will send a code, and the code is in the form of a change in the angle to the Bracelet used by the Deaf community in the form of vibration, the vibration at each prayer change will be different. Different vibration notifications on each Shalat movement can help the Deaf know the Imam's movement instructions.Furthermore, the prayer aids technology for the Deaf has a success rate of 89%. Thus, this tool can help the Deaf to perform congregational prayers.